Differences in competitive anxiety and perceived competence for high and low level competitive youth swimmers - McNamara, C. M. (1995)
Abstract: Differences among youth competitive swimmers in 'competitive trait anxiety', 'perceived athletic competence', and 'global self-worth' were examined for youth competitive swimmers who qualified or did not qualify for a championship meet as well as the differences for swimmers who move-up to a higher age level or not. Male and female 10 to 13 year old swimmers (N=151) who were members of United States Swimming (USS) participating on Boston area teams completed the Sport Competition Anxiety Test (SCAT) (Martens, 1977) and the Self-Perception Profile for Children (Harter, 1985). Utilizing 2x2 analysis of variance (qualify/non qualify and move-up or not) for each of the three dependent variables, no significant (p.05) interactions or main effects were found. The Pearson product-moment correlation coefficients among the dependent variables were all significant (p<.05). For youth competitive swimmers ages 10 to 13 years, as 'competitive trait anxiety' levels decreases, 'perceived athletic competence and 'global self-worth' levels increase. Furthermore, 'perceived athletic competence' and 'global self-worth' were found to be positively correlated. (McNamara, C.M. Differences in competitive anxiety and perceived competence for high and low level competitive youth swimmers, 1995. M.S., Springfield College. (137pp 2f $10.00) PSY 1853)